Control of Methicillin-Resistant Staphylococcus aureus Strains Associated With a Hospital Outbreak Involving Contamination From Anesthesia Equipment Using UV-C - Ochoa, Sara A.; Cruz-Córdova, Ariadnna; Mancilla-Rojano, Jetsi; Escalona-Venegas, Gerardo; Esteban-Kenel, Veronica; Franco-Hernández, Isabel; Parra-Ortega, Israel; Arellano-Galindo, José; Hernández-Castro, Rigoberto; Perez-López, Citlalli F.; De la Rosa-Zamboni, Daniela; Xicohtencatl-Cortes, Juan (Frontiers in Microbiology, 2020)
Methicillin-resistant Staphylococcus aureus (MRSA) is considered an opportunistic pathogen in humans and is mainly associated with healthcare-associated infections (HCAIs). This bacterium colonizes the skin and mucous membranes of healthy people and causes frequent hospital outbreaks. The aim of this study was to perform molecular typing of the staphylococcal cassette chromosome mec (SCCmec) and agr loci as wells as to establish the pulsotypes and clonal complexes (CCs) for MRSA and methicillin-sensitive S. aureus (MSSA) outbreaks associated with the operating room (OR) at a pediatric hospital. Twenty-five clinical strains of S. aureus (19 MRSA and six MSSA strains) were recovered from the outbreak (patients, anesthesia equipment, and nasopharyngeal exudates from external service anesthesia technicians). These clinical S. aureus strains were mainly resistant to benzylpenicillin (100%) and erythromycin (84%) and were susceptible to vancomycin and nitrofurantoin. The SCCmec type II was amplified in 84% of the S. aureus strains, and the most frequent type of the agr locus was agrII, which was amplified in 72% of the strains; however, the agrI and agrIII genes were mainly detected in MSSA strains. A pulsed-field gel electrophoresis (PFGE) analysis grouped the 25 strains into 16 pulsotypes (P), the most frequent of which was P1, including 10 MRSA strains related to the anesthesia equipment, external service anesthesia technicians, and hospitalized patients. Multilocus sequence typing (MLST) identified 15 sequence types (STs) distributed in nine CCs. The most prevalent ST was ST1011, belonging to CC5, which was associated with the SCCmec type II and agrII type. We postulate that the external service anesthesia technicians were MRSA carriers and that these strains were indirectly transmitted from the contaminated anesthesia equipment that was inappropriately disinfected. Finally, the MRSA outbreak was controlled when the anesthesia equipment disinfection was improved and hand hygiene was reinforced.